Green synthesis of silver nanoparticles using Arnebia nobilis root extract and wound healing potential of its hydrogel - Garg, Seema; Chandra, Amrish; Mazumder, Avijit; Mazumder, Rupa (Asian Journal of Pharmaceutics (AJP), 2014)
The present study reports wound healing potential of silver nanoparticles (AgNPs) hydrogel using Arnebia nobilis (A. nobilis) root extract. It makes a convenient method for the green synthesis of AgNPs and evaluated for its wound healing activity. Silver has been used for the treatment of medical ailments for over 100 years due to its natural antibacterial and antifungal properties. The synthesized nanoparticles were characterized using UV‑visible spectrophotometer; transmission electron microscopy, X‑ray diffraction (XRD), scanning electron microscopy, and Fourier transform infra‑red spectrometry. The nanoparticles were found to be mostly spherical in shape. XRD study shows that the particles are crystalline in nature with face centered cubic geometry. The synthesized AgNPs exhibited good antibacterial potential against both Gram‑positive and Gram‑negative bacterial strain as measured using well diffusion assay. The recent emergence of nanotechnology has provided a new therapeutic modality in AgNPs for use in wounds. We investigated the wound‑healing potential of AgNPs hydrogel using A. nobilis root extract in an excision animal model. The study showed that hydrogel of AgNPs using A. nobilis root extract exert positive effect due to their antimicrobial potential. The results provide insight into the mechanism of actions of AgNPs and have provided a novel therapeutic direction for wound treatment in the clinical practice. Key words: Antibacterial potential, Arnebia nobilis, Fourier transform infra‑red, silver nanoparticles, wound healing, X‑ray diffraction